Hyperthyroidism as a late effect in childhood cancer survivors - an Adult Life after Childhood Cancer in Scandinavia (ALiCCS) study. (1st February 2019) - Clausen, Camilla T.; Hasle, Henrik; Holmqvist, Anna S.; Madanat-Harjuoja, Laura; Tryggvadottir, Laufey; Wesenberg, Finn; Bautz, Andrea; Winther, Jeanette F.; Licht, Sofie de Fine
Abstract: Background : Hyperthyroidism is a rare disorder which may negatively affect health and quality of life. Its occurrence in childhood cancer survivors has not previously been investigated in detail. Material and methods : In the hospital registers of the five Nordic countries, 32, 944 childhood cancer survivors and 212, 675 population comparisons were followed for the diagnosis of hyperthyroidism. Hospitalisation rates, standardised hospitalisation rate ratios and absolute excess risks were calculated with 95% confidence intervals (CI). Results : Hyperthyroidism was diagnosed in 131 childhood cancer survivors, yielding an overall relative risk of 1.6 (95% CI: 1.3–1.9) compared with population comparisons. The risk was greatest 1–5 years after the diagnosis of cancer and in survivors of thyroid cancers, neuroblastomas, acute lymphoblastic leukaemia and Hodgkin lymphoma. Sixty-seven percent of survivors with hyperthyroidism had tumours located in the head, neck or upper body and half of survivors with hyperthyroidism were irradiated with 77% of them in the head and neck area. Conclusion : Childhood cancer survivors are at an increased risk of hyperthyroidism, potentially resulting in non-endocrine morbidity.